The Dynamics of Islamic Theology from the Classical to the Modern: The Dialectic of Revelation, Reason, and Inclusivism - Ardi, Hafidz; Samad , Duski; Mamad, Firdaus ST (The Future of Education Journal, 2025)
The development of Islamic theology (Ilmu Kalam) reflects a long intellectual journey shaped by political, social, and philosophical dynamics from the early period of Islam to the contemporary era. This article explores the evolution of theological thought ranging from classical schools such as the Khawarij, Mu’tazilah, Asy’ariyah, and Maturidiyah to modern inclusive theology. Using a qualitative library research method, this study examines how debates on divine justice, human free will, and the nature of God contributed to the emergence of various theological orientations. The findings reveal that classical theology emerged primarily as a response to political conflict and interaction with foreign philosophical traditions, especially Greek rationalism. In contrast, modern theology emphasizes inclusive, humanistic, and contextual approaches, represented by thinkers such as Nurcholish Madjid, Fazlur Rahman, and Hasan Hanafi. Their ideas shift theological discourse from a rigid, apologetic pattern toward a paradigm that promotes pluralism, social ethics, and interreligious engagement. This study concludes that Islamic theology remains dynamic and relevant, as it continues to negotiate between tradition and modernity, reason and revelation, and exclusivism and inclusivism.